Stance, Identity, and Marginalization: A Micro-ethnographic Study in an ESL Biology Classroom - Min-Seok Choi; Brian Seilstad (Cranmore Publishing, 2020)
Adolescent newcomer programs respond to superdiverse demographic shifts and, in the United States, are designed to support students with English language acquisition and preparation for mainstream or bilingual education. This eight-month ethnographic study examines a specific multilingual, multicultural group in an ESL biology classroom at a Central Ohio adolescent newcomer program and explores the stances group members take toward a Somali female student, Farin. Employing evaluating and positioning as stance-taking (Du Bois, 2007), we investigate how Farin's participation is evaluated and how her social identities are constructed in her group interaction. Over a series of classroom events, the group members take up regressive stances based on local ideologies about silence and appropriate group participation. These thicken over time despite various moves Farin makes to assert a positive group identity. This study underscores the potential consequences of teacher's evaluation of students'language in that students often employ the stance in constructing their relationships and identities, thus reinforcing particular ideologies associated with teacher's epistemic stance.